If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6b=(-42)
We move all terms to the left:
6b-((-42))=0
We add all the numbers together, and all the variables
6b+42=0
We move all terms containing b to the left, all other terms to the right
6b=-42
b=-42/6
b=-7
| 12-5x7=-13 | | 480=10(m+22) | | n/13=13 | | 49=7p+17 | | 7=t-868/13 | | 8x–38=6x-10 | | −41 a−4=47 a− | | h=3+h/5 | | 2=u/7-1 | | 19=6g-5 | | 2=z/8-1 | | 10.95=x-2.02 | | 6x–10=8x–38 | | p-390/20=29 | | d-690/27=10 | | 168+10b=978 | | 10=320/x | | (6x3)+5=35 | | 160=800-m | | 5x-31=2(4x-4)-2 | | 3x-(10-x)=22 | | X+17y=14 | | 246=47-x | | 2z÷7-5=0 | | 27=7k+3 | | 269=94-u | | 9x+9=10x+10 | | x+1.2=3.6 | | 4t^2-20t+1=0 | | -8a-19=-83 | | 2(4x+1)-4=3x+8 | | 4x+236=-232-9x |